Structural evolution characteristics and genesis of buried hill faults in the Chengdao–Zhuanghai area - Wang, Zhiwei; Zhang, Kai; Wu, Qunhu; Zhou, Hongke; Yu, Shina; Li, Yang (Frontiers in Earth Science, 2023)
The buried hills in the Chengdao–Zhuanghai area are rich in oil and gas resources, and their structures exhibit complex styles with unique evolutionary characteristics. Based on the most recent exploration progress in this region, the structural characteristics and active parameters of the buried hill faults in this region were quantitatively analyzed using the balanced section technique. In addition, the structural evolution process of the study area was reproduced by combining the structural-physical simulation experiment. Its spatio-temporal evolution characteristics and genesis mechanisms were also systematically investigated. As observed, the study area developed three basic sets of fault systems: the NW-trending extensional strike-slip fault, the NNE-trending left-handed compression–torsion fault, and the near-EW-trending extensional fault. The study area was further segmented into six buried hills: West Row Hill, Middle Row Hill, East Row Hill, Zhuanghai Buried Hill, Zhuangxi Buried Hill, and Changdi Buried Hill. The inner fault of the NW-trending Buried Hill is a strike-slip extensional fault that formed under the influence of the right-lateral strike-slip activity of the NW-trending Chengbei Fault from the Late Jurassic to the Early Cretaceous. In particular, the NNE-trending fault was a left-handed compression–torsion fault that formed under the left-handed strike-slip activity and regional compression stress field of the Tanlu fault zone. The near-EW fault was closely related to the near-SN extension stress field in the Late Cretaceous. Since the late Triassic, the study area has experienced six evolution stages, namely, overall uplift erosion (T3), overall coating deposition (J1+2), fault segmentation (J3-K1), extrusion uplift differentiation (K2), middle buried hill differentiation E), and overall stable subsidence (N-Q). Its tectonic evolution was primarily controlled by the significant variations in the tectonic stress field in the study area as well as its adjacent areas since the late Triassic, which were controlled by the tectonic stress field.